KEARIFAN LOKAL MASYARAKAT DESA KRINJING DALAM UPAYA MITIGASI BENCANA ERUPSI GUNUNG MERAPI - Satria Adjie; Andi Irwan Benardi (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2026)
LOCAL WISDOM OF THE KRINJING VILLAGE COMMUNITY IN MITIGATION EFFORTS TO MITIGATE THE DISASTER OF THE ERUPTION OF MOUNT MERAPI Indonesian society is certainly not far from local wisdom. This is especially true for communities living on the slopes of Volcano Merapi. This study was conducted in Krinjing Village, Dukun Subdistrict, Magelang Regency. The purpose of this study was to identify forms of local wisdom and their significance as a means of mitigating disasters caused by Volcano Merapi, and to obtain an overview of Krinjing Village, which is located in a disaster-prone area. This study used a descriptive qualitative approach as well as a spatial and environmental approach with data collection techniques of observation, interviews, and documentation. Local wisdom as mitigation includes Saparan, philosophy, slametan, and figures such as Wo Katorejo. Local wisdom as culture includes Wayangan, Jathilan, and Topeng Ireng. Community adaptation after the 2010 eruption includes the evacuation of sister villages to Deyangan Village, economic sector recovery, and the implementation of Standard Operating Procedures for preparedness. Local wisdom in Krinjing Village plays an important role in volcanic eruption mitigation by building solidarity and preparedness.